Preparation method of high-entropy alloy type negative electrode material for sodium ion battery

By mixing a variety of alloy-type metal powders with conductive carbon, high-energy ball milling and other treatment methods, and using polyimide derivatives as binders, the problem of volume expansion and insufficient conductivity of sodium-ion battery negative electrode materials during charging and discharging is solved, and the electrochemical performance of the battery is significantly improved.

CN120127131APending Publication Date: 2025-06-10ZHEJIANG HUAYU NADIAN NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202510332371.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2025-06-10

AI Technical Summary

Technical Problem

The negative electrode materials of existing sodium ion batteries are pulverized due to volume expansion during charging and discharging, resulting in electrode powderization and rupture of the interface phase film of solid electrolyte, which is insufficient electrical conductivity, which limits its practical application.

Method used

By mixing a variety of alloy-type metal powders with conductive carbon, using high-energy ball milling, high-speed stirring and dispersion, spray drying and annealing treatment, a high-entropy alloy-type negative electrode material with multiple heterostructures was prepared, and used with polyimide derivatives as binders.

Benefits of technology

It significantly improves the conductive properties of the material, reduces the volume expansion rate, improves the cycle stability and rate performance, and improves the overall electrochemical performance of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120127131A_ABST
    Figure CN120127131A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-entropy alloy type negative electrode material for a sodium ion battery. The preparation method comprises the following steps: grinding five kinds of metal powder of antimony powder, tin powder, bismuth powder, germanium powder, lead powder, iron powder, copper powder, nickel powder, aluminum powder and zinc powder and conductive carbon, performing high-energy ball milling, high-speed stirring dispersion, spray drying and annealing treatment in an inert atmosphere to obtain a negative electrode material, and preparing a negative electrode piece and a sodium ion battery from the negative electrode material and a binder. The binder comprises one or more of sodium alginate and a polyimide derivative, and the polyimide derivative is obtained by reacting 3-aminopropane-1-sulfonamide with 9, 9-bis (3, 4-dicarboxyphenyl) fluorene dianhydride. The preparation method is simple in process, low in cost and easy for large-scale production, and the prepared negative electrode material has multiple heterostructures and can effectively improve the conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrochemical technology, and particularly relates to a preparation method of a high-entropy alloy type anode material for sodium-ion batteries. Background Art

[0002] With the rapid development of the renewable energy and electric vehicle markets, sodium-ion batteries have become an important alternative to lithium-ion batteries due to their advantages of rich resources and low cost, in order to achieve efficient and low-cost energy storage solutions. However, the current mainstream hard carbon anode materials have limitations in energy density and are difficult to meet the market's demand for high-performance batteries; alloy type anode materials, such as tin, antimony, and phosphorus-based materials, although having high specific capacities, their problems such as electrode pulverization caused by volume expansion and the rupture of the solid electrolyte interface film during charge and discharge seriously limit their practical applications. Polyimide has been explored as a new binder due to its high mechanical strength and thermal stability. At the same time, existing polyimide binders still face problems such as insufficient conductivity and weak interfacial bonding with high-entropy alloys in sodium-ion batteries.

[0003] Therefore, exploring anode materials with high energy density has become the research focus. Alloy type anode materials, such as tin-based, germanium-based, and phosphorus-based ones, with their excellent theoretical specific capacities, have become the key to improving the energy density of sodium-ion batteries. Compared with hard carbon materials, alloy type anodes show higher potential in high-energy density sodium-ion batteries. Unfortunately, these materials face challenges such as drastic volume changes and poor conductivity in practical applications, which seriously restrict their commercialization process.

[0004] In view of the defects of alloy type anode materials, a variety of improvement strategies have been reported, including nanostructure design, composite material development, and electrolyte optimization, etc. These strategies have achieved certain results at the laboratory stage, but in the process of moving towards commercialization, their respective limitations have been exposed. CN117012924A discloses a self-supporting N-doped hollow biomass carbon Bi / SnO2@N-HCFs material and its preparation method and application, using nanometer technology. However, the high surface energy of nanomaterials is prone to cause agglomeration, and at the same time, it also increases production complexity and raises costs; CN118231611A discloses an alloy type anode material for sodium-ion batteries and its preparation method. Although the composite material design can partially alleviate the volume effect, the interfacial stability of the composite material is insufficient; CN118281194A discloses a bismuth / nitrogen-doped carbon nanosheet composite material with a sandwich-like array structure and its preparation method and application. Although the use of ether-based electrolytes can significantly improve the electrochemical performance of alloy type anode materials, the low decomposition voltage of such electrolytes makes it impossible to fully exert its performance advantages in full batteries.

[0005] Under this background, the present invention synthesizes a high-entropy alloy anode material with a multiple heterogeneous structure by mixing a variety of alloy-type anode materials and adopting a simple and easily industrialized high-energy ball milling method, effectively improving the electrical conductivity of the material and obtaining a series of high-entropy alloy-type anode materials with a low volume expansion rate to solve the problems of poor rate performance and unsatisfactory cycle life of this type of anode material. Summary of the Invention

[0006] The purpose of the present invention is to provide a preparation method of a high-entropy alloy-type anode material for a sodium-ion battery with a multiple heterogeneous structure and improved electrical conductivity.

[0007] The technical solution adopted by the present invention to achieve the above purpose is as follows: A high-entropy alloy-type anode material for a sodium-ion battery is a multiple heterogeneous structure product formed by the composite construction of metal powder and a conductive carbon matrix. Among them, The metal powder is one or more of antimony powder, tin powder, bismuth powder, germanium powder, lead powder, iron powder, copper powder, nickel powder, aluminum powder, and zinc powder. The conductive carbon is one or more of acetylene black, Ketjen black, Super P, carbon nanotubes, reduced graphene oxide, and carbon black. The multiple heterogeneous structure product has a single-phase solid solution with a grain size of 100-1500 nm.

[0008] Preferably, the mass ratio of the conductive carbon to the metal powder is 1-10:10-100.

[0009] A preparation method of a high-entropy alloy-type anode material for a sodium-ion battery includes the following preparation steps: obtaining a high-entropy alloy-type anode material for a sodium-ion battery by subjecting the metal powder and the conductive carbon matrix to high-energy ball milling, high-speed stirring and dispersion, spray drying, and annealing treatment. Among them, The metal powder is one or more of antimony powder, tin powder, bismuth powder, germanium powder, lead powder, iron powder, copper powder, nickel powder, aluminum powder, and zinc powder. The conductive carbon is one or more of acetylene black, Ketjen black, Super P, carbon nanotubes, reduced graphene oxide, and carbon black.

[0010] Preferably, the high-energy ball milling is carried out in an argon atmosphere, and the ball milling speed is 500-1200 rpm.

[0011] Preferably, the annealing temperature is 500-1100 °C, and the heating rate is 2-20 °C / min.

[0012] A negative electrode plate for a sodium-ion battery includes the high-entropy alloy-type anode material for a sodium-ion battery according to any one of claims 1-2.

[0013] Preferably, the negative electrode plate for a sodium-ion battery further contains a binder.

[0014] Preferably, the mass ratio of the high-entropy alloy type anode material for sodium-ion batteries to the binder is 630 - 3800:1 - 6.

[0015] Preferably, the binder is one or more of sodium alginate and polyimide derivatives.

[0016] Preferably, the polyimide derivative is obtained by reacting 3-aminopropane-1-sulfonamide with 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, and the mass ratio of 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride to 3-aminopropane-1-sulfonamide is 5.7 - 23:1.7 - 7. The polyimide derivative obtained by the reaction of 3-aminopropane-1-sulfonamide and 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride has high rigidity and thermal stability, can reduce the penetration of the electrolyte, inhibit the excessive growth of the solid electrolyte interface phase film, improve the cycle stability, and at the same time promote the sodium ion transport and reduce the electrode interface impedance. The anode electrode sheet of the sodium-ion battery obtained with the polyimide derivative as the binder has good electrical conductivity and stability, improving the overall electrochemical performance of the battery.

[0017] More preferably, N-(2-aminoethyl)-1,1-difluoromethanesulfonamide can also be added in the preparation of the polyimide derivative, and the mass-volume ratio of N-(2-aminoethyl)-1,1-difluoromethanesulfonamide to 3-aminopropane-1-sulfonamide is 2.2 - 8.8:1.7 - 7. N-(2-aminoethyl)-1,1-difluoromethanesulfonamide can serve as the active site of the polymerization reaction, participate in the polycondensation reaction of the polyimide, enhance the crosslinking degree of the molecular chain, optimize the performance of the polyimide binder, improve the interfacial bonding ability and ion transport function, and enhance the cycle stability and rate performance of the high-entropy alloy anode.

[0018] A sodium-ion battery includes a sodium-ion battery anode electrode sheet.

[0019] The present invention also provides a method for preparing a precursor slurry, including: Mixing and grinding metal powder and conductive carbon for 15 - 45 min to obtain precursor powder A; dissolving precursor powder A in deionized water, adding zirconia beads, and performing high-energy ball milling for 6 - 24 h under an argon atmosphere to obtain a uniformly distributed precursor slurry.

[0020] Preferably, the metal powder includes five of antimony powder, tin powder, bismuth powder, germanium powder, lead powder, iron powder, copper powder, nickel powder, aluminum powder, and zinc powder.

[0021] More preferably, the metal powder is antimony powder, tin powder, germanium powder, aluminum powder, and iron powder.

[0022] Preferably, the conductive carbon is one or more of acetylene black, Ketjen black, Super P, carbon nanotubes, reduced graphene oxide, and carbon black.

[0023] Preferably, the molar ratio between the five metal powders is 1-10:1-10:1-10:1-10:1-10.

[0024] Preferably, the mass ratio of the conductive carbon to the metal powder is 1-10:10-100.

[0025] Preferably, the mass ratio of the zirconia beads to the precursor powder A is 20-80:5-20.

[0026] Preferably, the ball milling speed is 500-1200 rpm.

[0027] Preferably, the particle size range of the precursor slurry is 100-1500 nm.

[0028] The present invention also provides a preparation method of a high-entropy alloy type negative electrode material for a sodium ion battery, including: Preparation of the high-entropy alloy type negative electrode material for a sodium ion battery: Dissolve the precursor slurry in deionized water, perform high-speed stirring and dispersion for 5-15 min to form a uniformly dispersed suspension, perform spray drying treatment and then secondary granulation to obtain a precursor powder B; in an argon atmosphere, anneal the precursor powder B for 2-12 h to obtain the high-entropy alloy type negative electrode material for a sodium ion battery.

[0029] Preferably, the mass-volume ratio of the precursor slurry to deionized water is 30-120 g:75-300 mL.

[0030] Preferably, the inlet air temperature of the spray drying is 160-220 °C, and the feeding speed is 10-100 mL / min.

[0031] Preferably, the annealing temperature is 500-1100 °C, and the heating rate is 2-20 °C / min.

[0032] The present invention also provides a preparation method of a negative electrode sheet for a sodium ion battery, including: Preparation of the negative electrode sheet for a sodium ion battery: Dissolve sodium alginate in deionized water to obtain a sodium alginate solution, mix the high-entropy alloy type negative electrode material for a sodium ion battery with the sodium alginate solution, fully grind and mix evenly, add zirconia beads, and perform vibration ball milling to obtain a mixed slurry. Coat the mixed slurry on an aluminum foil, and place it in a vacuum drying oven at 95-105 °C for vacuum drying for 4-8 h to obtain the negative electrode sheet for a sodium ion battery.

[0033] Preferably, the mass ratio of sodium alginate to deionized water is 1-6:32-194.

[0034] Preferably, the mass of the sodium alginate solution is measured by the mass of sodium alginate therein, and the mass ratio of the high-entropy alloy type negative electrode material for sodium ion battery to sodium alginate is 630 - 3800:1 - 6.

[0035] Preferably, the diameter of the zirconia beads is 2.5 - 3.5 mm.

[0036] The present invention also provides a method for preparing a negative electrode sheet of a sodium ion battery, including: Preparation of polyimide derivative: Dissolve 3-aminopropane-1-sulfonamide in N-methyl-2-pyrrolidone, stir for 30 min, under nitrogen protection and ice bath conditions, add 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, stir and react for 24 h, raise the temperature to 180 °C, continuously stir and introduce dry nitrogen to remove moisture, and react for 6 h to obtain the polyimide derivative.

[0037] Preferably, the mass-volume ratio of 3-aminopropane-1-sulfonamide to N-methyl-2-pyrrolidone is 1.7 - 7 g:50 - 200 mL.

[0038] Preferably, the mass ratio of 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride to 3-aminopropane-1-sulfonamide is 5.7 - 23:1.7 - 7.

[0039] Preparation of the negative electrode sheet of the sodium ion battery: Dissolve the polyimide derivative in N-methyl-2-pyrrolidone to obtain a polyimide derivative solution, mix the high-entropy alloy type negative electrode material for sodium ion battery with the polyimide derivative solution, fully grind and mix evenly, add zirconia beads, and vibrate and ball mill to obtain a mixed slurry. Coat the mixed slurry on the aluminum foil and place it in a vacuum drying oven at 95 - 105 °C for vacuum drying for 4 - 8 h to obtain the negative electrode sheet of the sodium ion battery.

[0040] Preferably, the mass ratio of the polyimide derivative to N-methyl-2-pyrrolidone is 1 - 6:32 - 194.

[0041] Preferably, the mass of the polyimide derivative solution is measured by the mass of the polyimide derivative therein, and the mass ratio of the high-entropy alloy type negative electrode material for sodium ion battery to sodium alginate is 630 - 3800:1 - 6.

[0042] Preferably, the diameter of the zirconia beads is 2.5 - 3.5 mm.

[0043] The present invention also provides a method for preparing a polyimide derivative, including: Preparation of polyimide derivative: Dissolve 3-aminopropane-1-sulfonamide and N-(2-aminoethyl)-1,1-difluoromethanesulfonamide in N-methyl-2-pyrrolidone, stir for 30 min, under nitrogen protection and ice bath conditions, add 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, stir and react for 24 h, raise the temperature to 180 °C, continuously stir and introduce dry nitrogen to remove moisture, react for 6 h to obtain the polyimide derivative.

[0044] Preferably, the mass-volume ratio of 3-aminopropane-1-sulfonamide to N-methyl-2-pyrrolidone is 1.7 - 7 g:50 - 200 mL.

[0045] Preferably, the mass-volume ratio of N-(2-aminoethyl)-1,1-difluoromethanesulfonamide to 3-aminopropane-1-sulfonamide is 2.2 - 8.8:1.7 - 7.

[0046] Preferably, the mass ratio of 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride to 3-aminopropane-1-sulfonamide is 5.7 - 23:1.7 - 7.

[0047] In the present invention, five metal powders are ground with conductive carbon, and through high-energy ball milling, high-speed stirring and dispersion, spray drying, and annealing treatment under an inert atmosphere, a negative electrode material is obtained. When preparing a negative electrode sheet and a sodium-ion battery with a binder, the following beneficial effects are achieved: The prepared negative electrode sheet has good conductivity and stability, and the electrochemical performance of the prepared sodium-ion battery is improved. Therefore, the present invention is a preparation method of a high-entropy alloy type negative electrode material for a sodium-ion battery with multiple heterogeneous structures and improved conductive performance. Description of the Drawings

[0048] Figure 1 It is a schematic diagram of a preparation method of a high-entropy alloy type negative electrode material for a sodium-ion battery. Detailed Embodiments

[0049] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts shall fall within the protection scope of the present invention.

[0050] The following first describes the concepts involved in the present application in conjunction with the accompanying drawings. It should be noted that the following description of each concept is only to make the content of the present application easier to understand, and does not limit the scope of protection of the present application; at the same time, the embodiments and features in the embodiments of the present application can be combined with each other in the absence of conflict. The present application will be described in detail with reference to the accompanying drawings and in conjunction with the embodiments.

[0051] Embodiment 1: Preparation of precursor slurry: Mix tin powder, antimony powder, germanium powder, bismuth powder, iron powder and acetylene black and grind for 30 minutes to obtain precursor powder A; dissolve precursor powder A in deionized water, add zirconium oxide beads, and perform high-energy ball milling for 12 hours under argon atmosphere to obtain a uniformly distributed precursor slurry. The mass ratio of tin powder to acetylene black is 11.9:3.2, the mass ratio of antimony powder to acetylene black is 12.2:3.2, the mass ratio of germanium powder to acetylene black is 7.3:3.2, the mass ratio of bismuth powder to acetylene black is 20.9:3.2, and the mass ratio of iron powder to acetylene black is 5.6:3.2; the mass of precursor powder A is measured by the mass of acetylene black therein, and the volume mass ratio of deionized water to acetylene black is 10mL:3.2g; the mass ratio of zirconium oxide beads to precursor powder A is 40:10, the ball milling speed is 1000rpm, and the D of the precursor slurry particles is 20.9:3.2. 50 The particle size is 250nm.

[0052] Preparation of high entropy alloy negative electrode material for sodium ion battery: Dissolve the precursor slurry in deionized water, stir and disperse at high speed for 10 minutes to form a uniformly dispersed suspension, spray dry and perform secondary granulation to obtain precursor powder B; anneal the precursor powder B for 6 hours in an argon atmosphere to obtain a high entropy alloy negative electrode material for sodium ion battery. The mass volume ratio of the precursor slurry to deionized water is 60g:150mL; the inlet air temperature of the spray drying is 180℃, and the feed rate is 10mL / min; the annealing temperature is 1000℃, and the heating rate is 10℃ / min.

[0053] Preparation of negative electrode sheet for sodium ion battery: Sodium alginate is dissolved in deionized water to obtain sodium alginate solution, high entropy alloy negative electrode material for sodium ion battery is mixed with sodium alginate solution, fully ground and mixed, zirconium oxide beads are added, and mixed slurry is obtained by vibration ball milling, and the mixed slurry is coated on aluminum foil, and vacuum dried in a vacuum drying oven at 100°C for 6 hours to obtain negative electrode sheet for sodium ion battery. The mass ratio of sodium alginate to deionized water is 3:97; the mass of sodium alginate solution is measured by the mass of sodium alginate therein, and the mass ratio of high entropy alloy negative electrode material for sodium ion battery to sodium alginate is 1900:3; the diameter of zirconium oxide beads is 3mm.

[0054] Example 2: Compared with Example 1, the only difference lies in the preparation of the precursor slurry.

[0055] Preparation of the precursor slurry: Tin powder, antimony powder, germanium powder, aluminum powder, iron powder and acetylene black were mixed and ground for 30 min to obtain precursor powder A; precursor powder A was dissolved in deionized water and subjected to high-energy ball milling for 12 h under an argon atmosphere to obtain a uniformly distributed precursor slurry. The mass ratio of tin powder to acetylene black was 11.9:3.2, the mass ratio of antimony powder to acetylene black was 12.2:3.2, the mass ratio of germanium powder to acetylene black was 7.3:3.2, the mass ratio of aluminum powder to acetylene black was 2.7:3.2, and the mass ratio of iron powder to acetylene black was 5.6:3.2; the mass of precursor powder A was measured based on the mass of acetylene black therein, the volume-mass ratio of deionized water to acetylene black was 10 mL:3.2 g, the ball milling speed was 1000 rpm, and the D 50 particle size of the precursor slurry was 250 nm.

[0056] Example 3: Compared with Example 1, the only difference lies in the preparation of the precursor slurry.

[0057] Preparation of the precursor slurry: Tin powder, antimony powder, germanium powder, bismuth powder, iron powder and acetylene black were mixed and ground for 30 min to obtain precursor powder A; precursor powder A was dissolved in deionized water and subjected to high-energy ball milling for 12 h under an argon atmosphere to obtain a uniformly distributed precursor slurry. The mass ratio of tin powder to acetylene black was 11.9:1.5, the mass ratio of antimony powder to acetylene black was 12.2:1.5, the mass ratio of germanium powder to acetylene black was 7.3:1.5, the mass ratio of bismuth powder to acetylene black was 20.9:1.5, and the mass ratio of iron powder to acetylene black was 5.6:1.5; the mass of precursor powder A was measured based on the mass of acetylene black therein, the volume-mass ratio of deionized water to acetylene black was 10 mL:1.5 g, the ball milling speed was 1000 rpm, and the D 50 particle size of the precursor slurry was 250 nm.

[0058] Example 4: Compared with Example 1, the only difference lies in the preparation of the precursor slurry.

[0059] Preparation of precursor slurry: Mix tin powder, antimony powder, germanium powder, bismuth powder, iron powder and acetylene black and grind them for 30 min to obtain precursor powder A; dissolve precursor powder A in deionized water and perform high-energy ball milling for 12 h under an argon atmosphere to obtain a uniformly distributed precursor slurry. The mass ratio of tin powder to acetylene black is 11.9:6, the mass ratio of antimony powder to acetylene black is 12.2:6, the mass ratio of germanium powder to acetylene black is 7.3:6, the mass ratio of bismuth powder to acetylene black is 20.9:6, and the mass ratio of iron powder to acetylene black is 5.6:6; the mass of precursor powder A is measured based on the mass of acetylene black therein, the volume-mass ratio of deionized water to acetylene black is 10 mL:6 g, the ball milling speed is 1000 rpm, and the D 50 particle size of the precursor slurry is 250 nm.

[0060] Example 5: The difference between this example and Example 1 lies only in the preparation of the precursor slurry.

[0061] Preparation of precursor slurry: Mix tin powder, antimony powder, germanium powder, bismuth powder, iron powder and acetylene black and grind them for 30 min to obtain precursor powder A; dissolve precursor powder A in deionized water and perform high-energy ball milling for 12 h under an argon atmosphere to obtain a uniformly distributed precursor slurry. The mass ratio of tin powder to acetylene black is 11.9:3.2, the mass ratio of antimony powder to acetylene black is 12.2:3.2, the mass ratio of germanium powder to acetylene black is 7.3:3.2, the mass ratio of bismuth powder to acetylene black is 20.9:3.2, and the mass ratio of iron powder to acetylene black is 5.6:3.2; the mass of precursor powder A is measured based on the mass of acetylene black therein, the volume-mass ratio of deionized water to acetylene black is 10 mL:3.2 g, the ball milling speed is 500 rpm, and the D 50 particle size of the precursor slurry is 250 nm.

[0062] Example 6: The difference between this example and Example 1 lies only in the preparation of the precursor slurry.

[0063] Preparation of precursor slurry: Mix tin powder, antimony powder, germanium powder, bismuth powder, iron powder and acetylene black and grind them for 30 min to obtain precursor powder A; dissolve precursor powder A in deionized water and perform high-energy ball milling for 12 h under an argon atmosphere to obtain a uniformly distributed precursor slurry. The mass ratio of tin powder to acetylene black is 11.9:3.2, the mass ratio of antimony powder to acetylene black is 12.2:3.2, the mass ratio of germanium powder to acetylene black is 7.3:3.2, the mass ratio of bismuth powder to acetylene black is 20.9:3.2, and the mass ratio of iron powder to acetylene black is 5.6:3.2; the mass of precursor powder A is measured based on the mass of acetylene black therein, the volume-mass ratio of deionized water to acetylene black is 10 mL:3.2 g, the ball milling speed is 800 rpm, and the D 50The particle size is 250 nm.

[0064] Example 7: Compared with Example 1, the only difference in this example lies in the preparation of the negative electrode sheet of the sodium-ion battery.

[0065] Preparation of the polyimide derivative: Dissolve 3-aminopropane-1-sulfonamide in N-methyl-2-pyrrolidone, stir for 30 min. Under nitrogen protection and ice bath conditions, add 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, and stir and react for 24 h. Raise the temperature to 180 °C, continuously stir and introduce dry nitrogen to remove moisture, and react for 6 h to obtain the polyimide derivative. The mass-volume ratio of 3-aminopropane-1-sulfonamide to N-methyl-2-pyrrolidone is 3.5 g:100 mL, and the mass ratio of 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride to 3-aminopropane-1-sulfonamide is 11.5:3.5.

[0066] Preparation of the negative electrode sheet of the sodium-ion battery: Dissolve the polyimide derivative in N-methyl-2-pyrrolidone to obtain a polyimide derivative solution. Mix the high-entropy alloy type negative electrode material for sodium-ion batteries with the polyimide derivative solution, fully grind and mix evenly, add zirconia beads, and vibrate and ball mill to obtain a mixed slurry. Coat the mixed slurry on aluminum foil and place it in a vacuum drying oven at 100 °C for vacuum drying for 6 h to obtain the negative electrode sheet of the sodium-ion battery. The mass ratio of the polyimide derivative to N-methyl-2-pyrrolidone is 3:97. The mass of the polyimide derivative solution is measured by the mass of the polyimide derivative therein. The mass ratio of the high-entropy alloy type negative electrode material for sodium-ion batteries to sodium alginate is 1900:3, and the diameter of the zirconia beads is 3 mm.

[0067] Example 8: Compared with Example 7, the only difference in this example lies in the preparation of the polyimide derivative.

[0068] Preparation of the polyimide derivative: Dissolve 3-aminopropane-1-sulfonamide in N-methyl-2-pyrrolidone, stir for 30 min. Under nitrogen protection and ice bath conditions, add 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, and stir and react for 24 h. Raise the temperature to 180 °C, continuously stir and introduce dry nitrogen to remove moisture, and react for 6 h to obtain the polyimide derivative. The mass-volume ratio of 3-aminopropane-1-sulfonamide to N-methyl-2-pyrrolidone is 3.5 g:100 mL, and the mass ratio of 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride to 3-aminopropane-1-sulfonamide is 17.2:3.5.

[0069] Example 9: Compared with Example 7, the only difference in this example lies in the preparation of the polyimide derivative.

[0070] Preparation of polyimide derivative: Dissolve 3-aminopropane-1-sulfonamide and N-(2-aminoethyl)-1,1-difluoromethanesulfonamide in N-methyl-2-pyrrolidone, stir for 30 min, and under nitrogen protection and ice bath conditions, add 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, stir and react for 24 h, raise the temperature to 180 °C, continuously stir and introduce dry nitrogen to remove moisture, and react for 6 h to obtain the polyimide derivative. The mass-volume ratio of 3-aminopropane-1-sulfonamide to N-methyl-2-pyrrolidone is 3.5 g:100 mL, the mass ratio of 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride to 3-aminopropane-1-sulfonamide is 11.5:3.5, and the mass ratio of N-(2-aminoethyl)-1,1-difluoromethanesulfonamide to 3-aminopropane-1-sulfonamide is 4.4:3.5.

[0071] Example 10: The difference between this example and Example 9 is only in the preparation of the polyimide derivative.

[0072] Preparation of polyimide derivative: Dissolve 3-aminopropane-1-sulfonamide and N-(2-aminoethyl)-1,1-difluoromethanesulfonamide in N-methyl-2-pyrrolidone, stir for 30 min, and under nitrogen protection and ice bath conditions, add 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, stir and react for 24 h, raise the temperature to 180 °C, continuously stir and introduce dry nitrogen to remove moisture, and react for 6 h to obtain the polyimide derivative. The mass-volume ratio of 3-aminopropane-1-sulfonamide to N-methyl-2-pyrrolidone is 3.5 g:100 mL, the mass ratio of 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride to 3-aminopropane-1-sulfonamide is 11.5:3.5, and the mass ratio of N-(2-aminoethyl)-1,1-difluoromethanesulfonamide to 3-aminopropane-1-sulfonamide is 8.8:3.5.

[0073] Comparative Example 1: The difference between this comparative example and Example 1 is only in the preparation of the precursor slurry.

[0074] Preparation of precursor slurry: Mix and grind tin powder and acetylene black for 30 min to obtain precursor powder A; dissolve precursor powder A in deionized water and perform high-energy ball milling for 12 h under an argon atmosphere to obtain a uniformly distributed precursor slurry. The mass ratio of tin powder to acetylene black is 59.5:3.2, the mass of precursor powder A is measured based on the mass of acetylene black therein, the volume-mass ratio of deionized water to acetylene black is 10 mL:3.2 g, the ball milling speed is 1000 rpm, and the D 50 particle size of the precursor slurry is 250 nm.

[0075] Comparative Example 2: This comparative example is different from Example 1 only in the preparation of the precursor slurry.

[0076] Preparation of the precursor slurry: Antimony powder and acetylene black were mixed and ground for 30 min to obtain precursor powder A; the precursor powder A was dissolved in deionized water and subjected to high-energy ball milling for 12 h under an argon atmosphere to obtain a uniformly distributed precursor slurry. The mass ratio of antimony powder to acetylene black was 61:3.2. The mass of the precursor powder A was measured based on the mass of the acetylene black therein. The volume-mass ratio of deionized water to acetylene black was 10 mL:3.2 g, the ball milling speed was 1000 rpm, and the D 50 particle size of the precursor slurry was 250 nm.

[0077] Comparative Example 3: This comparative example is different from Example 1 only in the preparation of the precursor slurry.

[0078] Preparation of the precursor slurry: Germanium powder and acetylene black were mixed and ground for 30 min to obtain precursor powder A; the precursor powder A was dissolved in deionized water and subjected to high-energy ball milling for 12 h under an argon atmosphere to obtain a uniformly distributed precursor slurry. The mass ratio of germanium powder to acetylene black was 36.5:3.2. The mass of the precursor powder A was measured based on the mass of the acetylene black therein. The volume-mass ratio of deionized water to acetylene black was 10 mL:3.2 g, the ball milling speed was 1000 rpm, and the D 50 particle size of the precursor slurry was 250 nm.

[0079] Comparative Example 4: This comparative example is different from Example 1 only in the preparation of the precursor slurry.

[0080] Preparation of the precursor slurry: Bismuth powder and acetylene black were mixed and ground for 30 min to obtain precursor powder A; the precursor powder A was dissolved in deionized water and subjected to high-energy ball milling for 12 h under an argon atmosphere to obtain a uniformly distributed precursor slurry. The mass ratio of bismuth powder to acetylene black was 104.5:3.2. The mass of the precursor powder A was measured based on the mass of the acetylene black therein. The volume-mass ratio of deionized water to acetylene black was 10 mL:3.2 g, the ball milling speed was 1000 rpm, and the D 50 particle size of the precursor slurry was 250 nm.

[0081] Comparative Example 5: This comparative example is different from Example 7 only in the preparation of the polyimide derivative.

[0082] Preparation of polyimide derivative: Dissolve acrylamide in N-methyl-2-pyrrolidone, stir for 30 min, under nitrogen protection and ice bath conditions, add 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, stir and react for 24 h, raise the temperature to 180 °C, continuously stir and introduce dry nitrogen to remove moisture, react for 6 h to obtain the polyimide derivative. The mass-volume ratio of acrylamide to N-methyl-2-pyrrolidone is 1.85 g:100 mL, and the mass ratio of 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride to acrylamide is 11.5:1.85.

[0083] Comparative Example 6: This comparative example is different from Example 7 only in the preparation of the polyimide derivative.

[0084] Preparation of polyimide derivative: Dissolve 3-aminopropane-1-sulfonamide in N-methyl-2-pyrrolidone, stir for 30 min, under nitrogen protection and ice bath conditions, add benzoic anhydride, stir and react for 24 h, raise the temperature to 180 °C, continuously stir and introduce dry nitrogen to remove moisture, react for 6 h to obtain the polyimide derivative. The mass-volume ratio of 3-aminopropane-1-sulfonamide to N-methyl-2-pyrrolidone is 3.5 g:100 mL, and the mass ratio of benzoic anhydride to 3-aminopropane-1-sulfonamide is 5.65:3.5.

[0085] Comparative Example 7: This comparative example is different from Example 7 only in the preparation of the polyimide derivative.

[0086] Preparation of polyimide derivative: Dissolve acrylamide in N-methyl-2-pyrrolidone, stir for 30 min, under nitrogen protection and ice bath conditions, add benzoic anhydride, stir and react for 24 h, raise the temperature to 180 °C, continuously stir and introduce dry nitrogen to remove moisture, react for 6 h to obtain the polyimide derivative. The mass-volume ratio of acrylamide to N-methyl-2-pyrrolidone is 1.85 g:100 mL, and the mass ratio of benzoic anhydride to acrylamide is 5.65:1.85.

[0087] Test Example 1: Reversible capacity performance test of button cells.

[0088] Test samples: Negative electrode sheets of sodium-ion batteries prepared in each example and comparative example.

[0089] Test method: 1 mol / L NaPF 6Using DME as the electrolyte, metallic sodium as the counter electrode, and the negative electrode sheet of the sodium-ion battery as the working electrode, a CR2032 coin-type battery was assembled in an inert atmosphere glove box. The Neware CT4000 test system was used with a voltage window of 0.01 - 2.0 V to record the capacity retention rate at different cycle numbers. Under the fully charged state, the deformation parameters of the electrode material were measured by a dilatometer.

[0090] The test results of the reversible capacity performance of the coin-type battery are shown in Table 1: Table 1 Test results of the reversible capacity performance of the coin-type battery Sample Volume expansion rate of the fully charged electrode (%) Reversible capacity at 0.1 A / g (mAh / g) Capacity retention rate after 200 cycles at 0.1 A / g (%) Reversible capacity at 1 A / g (mAh / g) Example 1 56 443 97 373 Example 2 53 320 96 305 Example 3 79 385 93 234 Example 4 50 412 87 298 Example 5 119 391 93 267 Example 6 94 425 91 309 Example 7 48 445 97 385 Example 8 47 449 97 398 Example 9 44 472 98 443 Example 10 41 481 99 452 Comparative Example 1 360 517 12 105 Comparative Example 2 259 439 13 94 Comparative Example 3 372 274 19 78 Comparative Example 4 294 288 17 73 Comparative Example 5 131 364 45 165 Comparative Example 6 143 327 42 160 Comparative Example 7 186 290 38 125 Examples 1-2 used five different metal powders for mixing. Different metals provide different capacities when participating in the electrochemical reaction, making the reversible capacity of Example 1 higher than that of Example 2. At the same time, the selection of different metal powders also has a certain impact on the volume change of the material during charge and discharge. After changing the mass ratio of metal powder to acetylene black in Examples 3-4, the volume expansion rate of the electrode sheet in the fully charged state increased, the reversible capacity at 0.1 A / g increased, and the capacity retention rate after 200 cycles and the reversible capacity at 1 A / g also decreased, indicating that this change in conditions affected the cycling and rate performance of the material while reducing volume expansion. After adjusting the ball milling speed in Examples 5-6, the significantly lower ball milling speed in Example 5 caused a substantial increase in the volume expansion rate and varying degrees of changes in various properties; the volume expansion rate in Example 6 also increased, and there were also differences from Example 1 in terms of reversible capacity, cycling stability, and rate performance, indicating that the ball milling speed has a great influence on the material properties, and inappropriate speed will reduce the comprehensive performance of the material. Examples 7-8 used polyimide derivatives as binders, further reducing the volume expansion rate of the electrode sheet in the fully charged state, increasing the reversible capacity, and improving the capacity retention rate after cycling 200 times at 0.1 A / g, thus enhancing the cycle life of the sodium-ion battery. In Examples 9-10, after introducing N-(2-aminoethyl)-1,1-difluoromethanesulfonamide, the degree of molecular chain crosslinking increased, the electrode expansion rate decreased, and the reversible capacity at 1 A / g reached the highest, indicating that the formed crosslinked structure can effectively inhibit volume expansion and maintain electrode integrity. Comparative Examples 1-10 mixed five metal powders. Comparative Examples 1-4 used a single alloy-type negative electrode material, resulting in a substantial increase in the volume expansion rate, and significant decreases in the reversible capacity, cycle life, and rate performance, significantly reducing the electrical conductivity of the material. This fully demonstrates that the high-entropy alloy-type negative electrode material prepared by the present invention using multiple metal powders can effectively reduce the volume expansion rate, significantly improve the electrical conductivity, cycling stability, and rate performance of the material, having obvious advantages. In Comparative Example 5, 3-aminopropane-1-sulfonamide was not used, and in Comparative Example 6, 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride was not used, resulting in an increase in the reduction peak current density, indicating that the interfacial side reactions were more intense and the electrochemical stability was poor. In Comparative Example 7, both 3-aminopropane-1-sulfonamide and 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride were not used. Due to the loose structure and poor conductivity of the binder, the electrode was severely pulverized and the capacity retention rate decreased significantly, indicating that the performance of the binder has an important impact on the performance of the negative electrode material of the sodium-ion battery. The binders such as sodium alginate and polyimide derivatives selected in the present invention can enhance the binding force between materials and improve the stability of the electrode.

[0091] Test Example 2: Testing the peel strength of the negative electrode sheet of the sodium-ion battery.

[0092] Test samples: Anode electrode sheets of sodium-ion batteries prepared in each example and comparative example.

[0093] Test method: Cut the anode electrode sheets of sodium-ion batteries into strip samples with a width of 1.5 cm and a length of 10 cm. Use a universal material testing machine equipped with a 180° peeling fixture. The test speed is 50 mm / min. Separate the electrode material surface from the aluminum foil current collector. Fix the material surface to the moving fixture and the aluminum foil to the static fixture. Record the maximum tensile force during the peeling process and measure the average peeling force of the anode electrode sheets of sodium-ion batteries.

[0094] The test results of the peeling strength of the anode electrode sheets of sodium-ion batteries are shown in Table 2: Table 2 Test results of the peeling strength of the anode electrode sheets of sodium-ion batteries

[0095] Compared with Example 1, Example 2 changed the composition of the five metal powders, and the peeling strength decreased, indicating that the change in the composition of the metal powders will affect the bonding force between the anode electrode sheet and the aluminum foil current collector. Examples 3-4 changed the mass ratio of the metal powder to acetylene black, and the peeling strength decreased in both cases, indicating that the ratio of the metal powder to acetylene black affects the pore structure and surface roughness of the negative electrode material, affects the penetration and distribution of the binder inside the material, and affects the peeling strength. After adjusting the ball milling speed in Examples 5-6, the peeling strength decreased in both cases, indicating that an appropriate ball milling speed can improve the mixing uniformity and affect the microstructure of the material. Examples 7-10 changed the type of binder. Compared with Example 7, Example 8 changed the mass ratio of 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride to 3-aminopropane-1-sulfonamide, and the peeling strength increased; compared with Examples 7-8, Examples 9-10 introduced N-(2-aminoethyl)-1,1-difluoromethanesulfonamide, and the peeling strength was even higher. This shows that the change in the composition of the polyimide derivative significantly affects the peeling strength of the anode electrode sheet. Optimizing the performance of the binder is beneficial to improving the interfacial bonding ability, making the anode electrode sheet more tightly bonded to the current collector and increasing the peeling force. In Comparative Examples 1-4, single metal powders were used, and a complex and synergistic structure like that of the high-entropy alloy could not be formed, and the interaction with the binder was weak, resulting in easier separation from the current collector during the peeling test. In Comparative Example 5, 3-aminopropane-1-sulfonamide was not used, and in Comparative Example 6, 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride was not used, and the electrode was severely pulverized and the peeling force decreased significantly. In Comparative Example 7, both 3-aminopropane-1-sulfonamide and 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride were not used, and the peeling strength reached the lowest, indicating that these two compounds play a key role in preparing polyimide derivatives with good peeling stability.

[0096] Test Example 3: Electrochemical impedance spectroscopy test of sodium-ion batteries.

[0097] Test samples: Anode electrodes of sodium-ion batteries prepared in each example and comparative example.

[0098] Test method: Using 1 mol / L NaPF 6 / DME as the electrolyte, metallic sodium as the counter electrode, and the anode electrode of the sodium-ion battery as the working electrode, assemble a CR2032-type button battery in an inert atmosphere glove box. Using an electrochemical workstation CHI660e, set an alternating current excitation signal with an amplitude of 5 - 10 mV and a frequency range of 10 kHz - 1 MHz. Record the corresponding current response, calculate the impedance modulus and phase angle, and fit to generate an electrochemical impedance spectrum.

[0099] The test results of the electrochemical impedance spectrum of the sodium-ion battery are shown in Table 3: Table 3 Test results of the electrochemical impedance spectrum of the sodium-ion battery

[0100] Compared with Example 1, the type of metal powder was changed in Example 2, and the mass of acetylene black was changed in Examples 3-4. The charge transfer resistance was increased in all cases, indicating that after changing the composition or proportion of the metal powder, the crystal structure and electron cloud distribution inside the material changed, affecting the smoothness of electron conduction. In Examples 5-6, the ball milling speed was changed. Too high or too low speed affected the particle size and mixing uniformity of the material, making it impossible to reduce the charge transfer resistance to an ideal level. Compared with Example 7, the mass ratio of 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride to 3-aminopropane-1-sulfonamide was changed in Example 8, and the charge transfer resistance was relatively reduced. Compared with Examples 7-8, after introducing N-(2-aminoethyl)-1,1-difluoromethanesulfonamide in Examples 9-10, the charge transfer resistance was significantly reduced. This indicates that during the charge and discharge process of the battery, the polyimide derivatives in Examples 9-10 are more conducive to the transfer of charges between the electrode material and the electrolyte, and the diffusion rate of ions in the electrode material is faster, meaning that their optimized interfacial charge transport performance is better and they can participate in electrochemical reactions more efficiently. In Comparative Examples 1-4, single metal materials were used, and the charge transfer resistance increased significantly, indicating that single metal powder cannot optimize the electron conduction path through the synergistic effect between multiple components like the high-entropy alloy composed of multiple metal powders, and cannot form a complex interfacial structure conducive to charge transfer. In Comparative Example 5, 3-aminopropane-1-sulfonamide was not used, and in Comparative Example 6, 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride was not used, resulting in an increase in the charge transfer resistance, indicating that it is difficult for charges to transfer between the electrode material and the electrolyte, and the interface is not conducive to charge transport, and the electrochemical performance is poor. In Comparative Example 7, neither 3-aminopropane-1-sulfonamide nor 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride was used, and the charge transfer resistance reached the highest level, significantly reducing the charge transport performance of the polyimide derivative and seriously affecting the battery performance, indicating that 3-aminopropane-1-sulfonamide and 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride play a key role in preparing polyimide derivatives with good charge transport performance and ion diffusion efficiency.

[0101] The above-described embodiments and / or implementation manners are only used to illustrate the preferred embodiments and / or implementation manners for implementing the technology of the present invention, and do not impose any formal restrictions on the implementation manners of the technology of the present invention. Any person skilled in the art, without departing from the scope of the technical means disclosed in the content of the present invention, may make some modifications or changes to other equivalent embodiments, but should still be regarded as the same technology or embodiment as the present invention in essence.

[0102] In this text, specific examples are used to illustrate the principles and implementation manners of the present application. The description of the above embodiments is only used to help understand the method and its core idea of the present application. The above is only the preferred implementation manner of the present application. It should be noted that due to the limited nature of literal expression and objectively infinite specific structures, for those of ordinary skill in the art, without departing from the principles of the present application, several improvements, refinements or changes can be made, or the above technical features can be combined in an appropriate manner; these improvements, refinements, changes or combinations, or directly applying the inventive concept and technical solution to other occasions without improvement, shall all be regarded as the protection scope of the present application.

Claims

1. A high entropy alloy negative electrode material for sodium ion batteries, a multi-heterogeneous structure product formed by a composite of metal powder and a conductive carbon matrix, wherein: The metal powder is one or more of antimony powder, tin powder, bismuth powder, germanium powder, lead powder, iron powder, copper powder, nickel powder, aluminum powder and zinc powder. The conductive carbon is one or more of acetylene black, Ketjen black, Super P, carbon nanotubes, reduced graphene oxide and carbon black. The multiple heterostructure product has a single-phase solid solution with a grain size of 100-1500 nm.

2. A high entropy alloy negative electrode material for sodium ion battery according to claim 1, characterized in that: The mass ratio of the conductive carbon to the metal powder is 1-10:10-100.

3. A method for preparing a high entropy alloy negative electrode material for a sodium ion battery, comprising the following preparation steps: The metal powder and the conductive carbon matrix are subjected to high-energy ball milling, high-speed stirring dispersion, spray drying and annealing to obtain a high-entropy alloy negative electrode material for sodium ion batteries, wherein: The metal powder is one or more of antimony powder, tin powder, bismuth powder, germanium powder, lead powder, iron powder, copper powder, nickel powder, aluminum powder and zinc powder. The conductive carbon is one or more of acetylene black, Ketjen black, Super P, carbon nanotubes, reduced graphene oxide and carbon black.

4. The method for preparing a high entropy alloy negative electrode material for a sodium ion battery according to claim 3, characterized in that: The high energy ball milling is carried out in an argon atmosphere at a rotation speed of 500-1200 rpm.

5. The method for preparing a high entropy alloy negative electrode material for a sodium ion battery according to claim 3, characterized in that: The annealing temperature is 500-1100° C., and the heating rate is 2-20° C. / min.

6. A negative electrode plate for a sodium ion battery, comprising the high entropy alloy negative electrode material for a sodium ion battery according to any one of claims 1 to 2.

7. A sodium ion battery negative electrode sheet according to claim 6, characterized in that: The negative electrode plate of the sodium ion battery also contains a binder, and the mass ratio of the high entropy alloy negative electrode material for the sodium ion battery to the binder is 630-3800:1-6.

8. The negative electrode plate of a sodium ion battery according to claim 6, characterized in that: The sodium ion battery negative electrode plate also contains a binder, and the binder is one or more of sodium alginate and polyimide derivatives.

9. A sodium ion battery negative electrode sheet according to claim 8, characterized in that: The polyimide derivative is obtained by reacting 3-aminopropane-1-sulfonamide with 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, and the mass ratio of 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride to 3-aminopropane-1-sulfonamide is 5.7-23:1.7-7.

10. A sodium ion battery, comprising the sodium ion battery negative electrode sheet according to any one of claims 6 to 9.

Citation Information

Patent Citations

  • Self-standing N-doped hollow biomass carbon Bi / SnO2-coated N-HCFs material as well as preparation method and application thereof

    CN117012924A

  • Alloy type negative electrode material for sodium-ion battery and preparation method of alloy type negative electrode material

    CN118231611A

  • Bismuth / nitrogen-doped carbon nanosheet composite material with sandwich-like array structure as well as preparation method and application of bismuth / nitrogen-doped carbon nanosheet composite material

    CN118281194A

Cited By

  • Composite formula and preparation process of high-entropy negative electrode material of lead-lithium battery

    CN122202237A